Comparative features in Islamic architecture - Kabila Fares al-Maliki (Iraqi Journal of Architecture and Planning, 2009)
Most ofthe recent architectural studies directed towered the necessity of usingthe architectural characterization of the cultural inhlrited ofthe Islamic Architecturiin the futurist designs, in away that unified the contemporary architecture with thehistorical roots.The contemporary architecture environment ofthe types and styles various infunctions, forms and goals pushing on limitation of copying these types of traditionalarchitectural elements , but trying to study and realize the cognitional meanings andusing architectural solutions that had specific characterizations which connected withthe theoretical believes which came from the cultural environment ofthe Islamiccommunity in the contemporary designs.For that need ,for the designers to use the character of the IslamicArchitecture in the contemporary designs depending on architectural studies searchingin these meanings which must be objectively and comprehensively for (architecturalstudies and researches) and (practical topics in the contemporary architecture).Monumentality is one of these meanings, which is related to the culturalenvironment that needs an objectively comprehensive study.The absence of the cognitional frame was the main problem ol the researchthat is related to the monumentality in the Islamic Architecture.For that the main target ofthe research was to put the cognitional frame oftheMonumentality in Architecture so it can judge any type or style in architectureincluding Islamic Architecture.The research studied three tlpes of architecture (Babylon, Roman and Gothic)focussing basically and intensively on its Monumentality in its architecture to give thecognitional frame of the Monumentalitv in ils meaning , intentions , goals and itstopics in architecture, so it can judge any architecture including Islamic Architecturewhich had special characteristic that are specialized the Monumentality in IslamicArchitecture in comparison with other Architectures.